2019
DOI: 10.1002/humu.23730
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interpretation and clinical translation of minor genes related to Brugada syndrome

Abstract: Brugada syndrome (BrS) is an inherited arrhythmogenic disease associated with sudden cardiac death. The main gene is SCN5A. Additional variants in 42 other genes have been reported as deleterious, although these variants have not yet received comprehensive pathogenic analysis. Our aim was to clarify the role of all currently reported variants in minor genes associated with BrS. We performed a comprehensive analysis according to the American College of Medical Genetics and Genomics guidelines of published clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…The gene SEMA3A is involved in neuronal development and function, and it is currently included in some BrS diagnostic panels [98]. A PubMed search for "SEMA3A AND Brugada syndrome" on October 7, 2019 resulted in only three results: a meta-analysis in which only two variants in SEMA3A were identified out of 128 publications reporting 43 genes potentially associated with BrS [116], a review [98], and functional studies on cardiomyocytes derived from human-induced pluripotent stem cells [67]. In fact, a recent study contested the validity of the SEMA3A gene being included in BrS diagnostic panels [17].…”
Section: Other Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene SEMA3A is involved in neuronal development and function, and it is currently included in some BrS diagnostic panels [98]. A PubMed search for "SEMA3A AND Brugada syndrome" on October 7, 2019 resulted in only three results: a meta-analysis in which only two variants in SEMA3A were identified out of 128 publications reporting 43 genes potentially associated with BrS [116], a review [98], and functional studies on cardiomyocytes derived from human-induced pluripotent stem cells [67]. In fact, a recent study contested the validity of the SEMA3A gene being included in BrS diagnostic panels [17].…”
Section: Other Genesmentioning
confidence: 99%
“…Similarly, while the gene FGF12 is currently included in diagnostic panels [98], a PubMed search for "FGF12 AND Brugada syndrome" on October 7, 2019 resulted in only two results: a review [98] and a study in which a variant in FGF12 was found in a single patient [117]. Finally, while the gene SLMAP is currently included in diagnostic panels [98], a PubMed search for "SLMAP AND Brugada syndrome" on October 7, 2019 resulted in only four results: a review [98], functional studies in transgenic mice [68], a meta-analysis that described finding two variants among 128 publications reporting 42 genes potentially associated with BrS [116], and the study to which the meta-analysis seems to be referring [118]. The SLMAP gene has been recently disputed as causative of BrS, lacking systematic, evidence-based evaluations as to the association between this gene and BrS, while in this same study, the genes SEMA3A and FGF12 did not even meet the criteria to be evaluated to be determined whether they could be potentially causative of BrS [17].…”
Section: Other Genesmentioning
confidence: 99%
“…SCN5A is considered pathogenic [ 15 ] despite only a few nonsynonymous variants that are considered deleterious [ 16 ]. Beyond SCN5A , pathogenic variants associated with BrS are in four minor genes: SLMAP , SEMA3A , SCNN1A , and SCN2B [ 17 ].…”
Section: Brugada Syndromementioning
confidence: 99%
“…Therefore, current guidelines for IAS recommend analysis of these five genes [ 10 ], although every year, new genes are associated with IAS. Further, recent studies showed that larger panels, including genes with limited association with IAS, provided minimal diagnostic yield, but increased the detection of variants classified with ambiguous clinical significance (variant of unknown significance, VUS) [ 11 , 17 ]. Therefore, careful interpretation of genetic tests is critical to appropriately care for patients and their relatives.…”
Section: Genetic Diagnosismentioning
confidence: 99%
“…While variants in more than 40 genes have been reported in association with BrS (Campuzano et al, 2019), the most robust evidence for pathogenicity is associated with SCN5A , the gene encoding NaV1.5, the α‐subunit of the cardiac sodium channel (Hosseini et al, 2018). In vitro functional assessment has demonstrated that the majority of BrS‐associated SCN5A variants lead to attenuation of the sodium current ( I Na ), although the extent of loss‐of‐function varies widely (Denham et al, 2018; Glazer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%